2017
DOI: 10.1007/s12253-017-0206-6
|View full text |Cite
|
Sign up to set email alerts
|

Much More than Trousseau Syndrome. The Broad Spectrum of the Pancreatic Paraneoplastic Syndromes

Abstract: When 150 years ago Armand Trousseau proposed that some thrombotic events might be the first sign of concealed visceral malignancies, these findings seemed to be just of anecdotal interest. Since then, however, we have learned that adenocarcinomas, including pancreatic cancers could be associated with a wide spectrum of paraneoplastic syndromes. They may precede the detection of the tumor, may occur simultaneously or may develop during its progression. Due to various hematologic, endocrine, cutaneous, articular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 71 publications
0
10
1
Order By: Relevance
“…In pancreatic cancer, significantly elevated plasma levels of fibrinogen, factor (F)VIII and D-dimer have been observed, whereas diminished levels of protein C and antithrombin III have been reported, although levels might change during tumour progression. 28 , 29 More importantly, pancreatic cancer cells directly produce a number of factors, or influence a number of activities, that promote coagulation (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatic cancer, significantly elevated plasma levels of fibrinogen, factor (F)VIII and D-dimer have been observed, whereas diminished levels of protein C and antithrombin III have been reported, although levels might change during tumour progression. 28 , 29 More importantly, pancreatic cancer cells directly produce a number of factors, or influence a number of activities, that promote coagulation (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence and development of liver cancer are related to many factors. In the developed countries, such as Europe and United States, obesity, adult diabetes and internal environmental disorders are the main stimulating factors of liver cancer, while in the developing countries, hepatitis viruses (HBV and HCV), long-term intake of ethanol, and aflatoxin-contaminated food play an important role in the formation of liver cancer 4,5. Surgical resection is the preferred option for early-stage liver cancer patients and confers 5-year survival rates of 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Since Armand Trousseau's proposal 150 years ago that thrombotic events may be the first sign of concealed visceral malignancies (Zalatnai et al, 2018), the relationship between cancer and vascular infarction events has been investigated. Although the cause of TS remains unclear, recent studies have shown that the role of the tumor itself, the effect of hypercoagulability, and the side effects of tumor-related treatment may be the causes of the disease.…”
Section: Discussionmentioning
confidence: 99%